Sustainability in the maritime industry : a collection of relevant papers - Delpizzo, Rich; Wang, Haifeng; Panek, Andrew (Society of Naval Architects and Marine Engineers, 2011)
These papers touch on the many different areas new regulations impact, from emission control of ships operating in international waters, to environmental impacts in the shipyard. This collection represents over thirty years of technical information from various venues and contains both practical and theoretical knowledge pertaining to energy efficiency, sustainable design and environmental impact in marine design. It is a valuable compilation of technical information on a wide range of topics to increase the knowledge base of marine engineers and designers in both operation and design, addressing marine environmental and sustainability concerns that have become an increasingly crucial aspect to operating in today's maritime industry.